Digitalization of Business Law: Urgency and Orientation of the Industrial Revolution 4.0 and Society 5.0 - I Gede Agus Kurniawan (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2022)
The digitalization of business law is one of the impacts of the development of technology and information. The development of technology and information is identical to the phenomenon of digitization, especially in the context of legal practice. This research gap is the existence of voids and overlapping legal rules related to technological developments in business where there should be legal rules that are general in nature and can accommodate business developments. This study aims to analyze the urgency and orientation of business law in the midst of the development of technology and information, especially with the development of the industrial revolution 4.0 and society 5.0. This research is a normative legal research. The results of the study confirm that the urgency of digitizing business law is by establishing laws and regulations that are in accordance with the needs of digitizing business law as well as the need for harmonization and revision of various existing regulations so that the law. In this case, the law can meet the demands of digital business practices in society. Laws in this case are regulations made by the central government to regulate and anticipate developments in business law so that one law with another may not overlap which has an impact on legal uncertainty in society. The orientation of business law in treading the era of the industrial revolution 4.0 and society 5.0 is that business law, especially business contracts, will become an instrument that is often used, especially digital business contract instruments. Furthermore, it is necessary to harmonize and even establish various laws and regulations using the omnibus law method to facilitate various overlapping laws and regulations as well as efforts to facilitate business development.